Metaplastic Paneth Cells in Extra-Intestinal Mucosal Niche Indicate a Link to Microbiome and Inflammation - Singh, Rajbir; Balasubramanian, Iyshwarya; Zhang, Lanjing; Gao, Nan (Frontiers in Physiology, 2020)
Paneth cells are residents of the intestinal epithelium. Abnormal appearance of Paneth cells has been widely documented in non-intestinal tissues within the digestive tract and even observed in non-gastrointestinal organs. Although metaplastic Paneth cells are part of the overarching pathology of intestinal metaplasia, only a fraction of intestinal metaplastic lesions contain Paneth cells. We survey literature documenting metaplastic Paneth cells to gain insights into mechanism underlying their etiologic development as well as their potential relevance to human health. A synthesized view from this study suggests that the emergence of metaplastic Paneth cells at extra-intestinal mucosal sites likely represents a protective, anti-bacterial, and inflammatory response evoked by an altered microbial activity.